Systemic Lupus Erythematosus Presenting with Cholestatic Jaundice and Hepatic Involvement: An Etiology Not to Be Overlooked: A Case Report and Literature Review - aouroud, hala; Meryem, Aouroud; Ezzahra, Fatima; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2023)
We present the case of a 33-year-old female patient who was admitted for evaluation of cholestatic jaundice, dark urine, pale stools, and generalized, persistent pruritus. Her symptoms had been ongoing for the past 3 months, with no history of exposure to toxic substances, hepatotoxic medications, or medicinal herbs. Additionally, she reported atypical right upper quadrant abdominal pain and inflammatory polyarthralgia. Laboratory investigations revealed normochromic normocytic aregenerative anemia (hemoglobin 8.9 g/dL), normal white blood cell count, and normal platelet count. Her C-reactive protein (CRP) was markedly elevated at 66 mg/L, and alanine transaminase (ALT) and aspartate transaminase (AST) levels were five times the upper limit of normal. Gamma-glutamyl transferase (GGT) was eight times the upper limit of normal, alkaline phosphatase (ALP) was 13 times the upper limit of normal, and total bilirubin was predominantly conjugated (136 µmol/L). Prothrombin time (PT) was within the normal range at 88%. Abdominal imaging studies, including liver, portal vein, and hepatic veins, revealed no anomalies. Serological tests for hepatitis A, B, and C were negative. Autoimmune serology showed a positive antinuclear antibody (ANA) titer of 1/520, positive anti-double-stranded DNA (anti-dsDNA) antibodies, and positive anti-Smith (anti-sm) antibodies. Further investigations for autoimmune hepatitis were negative. A diagnosis of systemic lupus erythematosus (SLE) with hepatic involvement was established.